2004
DOI: 10.1093/treephys/24.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen storage and its interaction with carbohydrates of young apple trees in response to nitrogen supply

Abstract: Bench-grafted 'Fuji/M.26' apple (Malus domestica Borkh.) trees received a constant nitrogen (N) supply (10.7 mM) from bud break to the end of June, and were then fertigated with 0, 5, 10, 15 or 20 mM N in a modified Hoagland's solution for 2 months during the summer. In mid-October, half of the trees fertigated at each N concentration were sprayed twice with 3% urea, whereas the remaining trees served as controls. All trees were harvested after natural leaf fall and were stored at 2 degrees C. Five trees from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 24 publications
6
48
0
7
Order By: Relevance
“…Similar results have been reported in an earlier study (Hamerlynck et al, 2004). Cheng et al (2004) have also found that as the N supply increases, the amounts of N in both free amino acids and proteins increase whereas the C/N ratio decreases. Water stress together with fertilization increased WUE (i.e., ␦ 13 C) in poplars, this result is consistent with previous studies (Brück et al, 2000;Welander and Ottosson, 2000;Li et al, 2003;Kondo et al, 2004) stating that WUE is significantly lower in well-watered treatments than in waterstressed treatments, but it increases with an increasing nutrient supply.…”
Section: Tablesupporting
confidence: 91%
“…Similar results have been reported in an earlier study (Hamerlynck et al, 2004). Cheng et al (2004) have also found that as the N supply increases, the amounts of N in both free amino acids and proteins increase whereas the C/N ratio decreases. Water stress together with fertilization increased WUE (i.e., ␦ 13 C) in poplars, this result is consistent with previous studies (Brück et al, 2000;Welander and Ottosson, 2000;Li et al, 2003;Kondo et al, 2004) stating that WUE is significantly lower in well-watered treatments than in waterstressed treatments, but it increases with an increasing nutrient supply.…”
Section: Tablesupporting
confidence: 91%
“…N is the mineral nutrient for which vines have the greatest demand and the nutrient that most often limits growth (Keller 2010). Differences in vegetative growth and yield were mainly determined by reserve N and not CHO (Cheng et al 2004). Nitrogen and carbon are incorporated together in many physiologically important plant compounds such as amino acids, proteins, and enzymes (Kozlowski and Pallardy 1997).…”
mentioning
confidence: 99%
“…앞서 언급한 바와 같이 사과나무의 내동성은 수체 내 탄수화물(carbohydrate)과 질소(nitrogen)의 함량에 영 향을 받지만 (Schupp et al, 2001), 탄수화물과 질소의 비 율인 C/N율에 의해서도 영향을 받는다 (Cheng, 2002;Cheng et al, 2004). 일반적으로 탄수화물은 단당류, 과 당류 및 다당류의 3가지 군으로 크게 나눌 수 있으며 (Byun et al, 2006), 식물 체내에 단당류 혹은 이당류가 많을수록 식물의 내동성은 증가하지만 다당류인 전분이 많으면 감소되는 것으로 알려져 있다 (Chae et al, 2006).…”
Section: 또한 사과나무의 내동성은 품종 대목의 종류 나무 의 부위 및 수체 내 영양 상태에 따라서도 달라질 수 있다unclassified